TINJAUAN YURIDIS MENGENAI TINDAK PIDANA YANG DITUNTUT DENGAN PASAL 351 (3) KUHP STUDI KASUS PUTUSAN MA NO. 1043 K/PID/2016 - Saputra, Rahmat (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2018)
The purpose of this study was to provide an overview of the actions of the defendant already fulfilling the elements of Article 351 paragraph (3) of the Criminal Code in the Supreme Court Decision No. 1043 K / PID / 2016 and to illustrate the basic consideration of the judge in imposing a verdict on a criminal offense charged with Article 351 paragraph (3) of the Criminal Code in the Supreme Court decision No. 1043 K / PID / 2016. The method used in this study is normative law research. Data collection methods in this study were carried out with literature study, which is a method of collecting data by searching and reviewing library materials (literature, research results, scientific magazines, scientific bulletins, scientific journals). Data collection techniques using qualitative analysis methods. The conclusion in this study is the application of material criminal law by the Panel of Judges of the Supreme Court in the case of Number 1043 K / PID / 2016 which corrected the decision of the Banjarmasin High Court Number 59 / PID / 2016 / PT.BJM, dated 13 July 2016 which strengthened the Kotabaru District Court Decision Number 64 / Pid.B/2016/PN. Ktb, dated April 27, 2016 stating that the defendant Nanang Ramli bin (late) Syamsudin was proven legally and convincingly guilty of committing a criminal act of maltreatment which resulted in the death of the victim Jumadi alias jumai bin yahya ( alm) as stipulated in Article 351 paragraph (3) the Penal Code (hereinafter referred to as the Criminal Code) is correct, it is in accordance with the Public Prosecutor's Subsidies indictment, and has been based on the facts of the trial, the evidence presented The Public Prosecutor is in the form of witness statements, evidence, post mortem, and statements of the defendant. The Panel of Judges of the Kotabaru District Court in its consideration there are still some shortcomings, especially in its subjective considerations, namely on consideration of things that are burdensome and matters that alleviate the defendant. The consideration used by the judge in this case only focuses on the perpetrators of the crime. Whereas Article 5 paragraph (1) of Law Number 48 Year concerning Judicial Power requires judges to explore, follow, and understand the legal values ​​and sense of justice that lives in society. This means that the judge must also consider the loss of the crime victim, and the community